2011
DOI: 10.1089/jpm.2010.0331
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Combined Hospice Care on Terminal Cancer Patients

Abstract: Background: Many patients with advanced cancer will develop physical and psychological symptoms related to their disease. These symptoms are infrequently treated by conventional care. Palliative care programs have been developed to fill this gap in care. However, there are limited beds in hospice units. To allow more terminal cancer patients to receive care from a hospice team, a combined hospice care system was recently developed in Taiwan. This study is a report of our experiences with this system. Patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 39 publications
2
32
0
Order By: Relevance
“…The chaplain who is a PCCS team member routinely provided emotional and spiritual support to patients and family members even when hospice wards were not available [13]. The major symptoms presented by terminal patients were pain (58 %), dyspnea (52 %), constipation (45 %), and fatigue (23 %) [9]. Chang et al conducted a retrospective study recruiting 313 terminal cancer patients from March 2005 to January 2006 and showed that the patients who received home care had better performance status, less shortness of breath, less limb swelling, less flatulence, and less constipation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The chaplain who is a PCCS team member routinely provided emotional and spiritual support to patients and family members even when hospice wards were not available [13]. The major symptoms presented by terminal patients were pain (58 %), dyspnea (52 %), constipation (45 %), and fatigue (23 %) [9]. Chang et al conducted a retrospective study recruiting 313 terminal cancer patients from March 2005 to January 2006 and showed that the patients who received home care had better performance status, less shortness of breath, less limb swelling, less flatulence, and less constipation.…”
Section: Discussionmentioning
confidence: 99%
“…Chou et al conducted a retrospective study in terminal cancer patients receiving PCCS in Taiwan and identified that lower disease awareness was associated with older age (age>75 years versus age=18-65 years), referral from nononcology departments, and primary cancer localization (lung, colon-rectum, or urological versus liver) [7]. Loke et al identified that there was a significant improvement in the rate of DNR signed orders from 41.5 to 71.5 % (p<0.0001), in the awareness of disease prognosis from 46.1 to 57.7 % (p=0.0006), and in hospice utilization by terminal cancer patients after receiving combined hospice care [9]. Tsai et al demonstrated that most common sites of primary cancer in terminal cancer patients admitted to the palliative care unit were lung (23.4 %), liver (15.6 %), and stomach (13 %).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Recent studies also demonstrate that meeting national care standards reduces hospital admissions and deaths for patients and that combining hospice care with acute care for terminal cancer patients can improve quality of life. 12,13 Studies in high-resource areas also demonstrate that early palliative care for oncology patients can decrease the use of anticancer treatments in the last 30 days of life. 14,15 Such studies are not routinely conducted in low-resource countries, 16 which are 84 countries classified by the World Bank as low and lower middle-income countries.…”
Section: Introductionmentioning
confidence: 99%
“… 3 However, the use of DNR orders may be complicated by ethnical, cultural, economic, and family values. Therefore, combining clinical and hospice care in the acute ward can enhance the acceptance of DNR, 4 as well as natural death. 5…”
Section: Introductionmentioning
confidence: 99%